APLIKASI PENDATAAN BARANG INVENTARIS LAB KOMPUTER UNIVERSITAS CITRA BANGSA KUPANG BERBASIS WEB - Abraham Gerald Tibuludji; Dewi Anggraini; Heni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABRAHAM GERALD TIBULUDJI, Web-Based Inventory Data Collection Application for Citra Bangsa University Kupang Computer Lab. Supervised by DEWI ANGGRAINI and HENI. Assets management or inventory management in the computer laboratory at Citra Bangsa University (UCB) Kupang which is still done manually with ledgers and spreadsheets has caused serious problems such as data inaccuracy, slow asset tracking, and loss of items, thus hampering operational effectiveness and accountability. Based on the literature review, a web-based information system solution with a Waterfall structured development methodology has proven effective in producing asset inventory application software that can improve the accuracy, efficiency, and transparency of inventory management. Therefore, this research aims to develop an integrated